Aplikasi Teori Personal Selling: Kasus pada Bank Regional - Meria Sri Primariyanti; Egi Arvian Firmansyah (University of Darussalam Gontor, 2017)
This research is a descriptive research aiming at knowing the implementationof bjb SurePrize program at bank bjb (bank Jabar Banten) Cianjur branchwhich is seen from the framework of personal selling theory. In addition, thisresearch is also aimed at determining the growth rate (trend) of savings anddemand deposits at bank bjb in the period of enactment of bjb SurePrize program.The research methods used are interview and literature study. The resultsshowed that the implementation of personal selling in the bjbSurePrizeprogram at bank bjb Cianjur branch is executed by executive personal selling,inside personal selling and outside personal selling. Personal sellingprocess conducted uses 6 (six) stages, namely: prospecting, pre-approach,presentation and demonstration, overcoming objections, closing and followup. In addition, there is also a contribution from the bjb SurePrize program.on the growth of savings and demand deposits in the year 2016 of 0.16%.